Unravelling the Tapestry: A Literature Review on the History of Yemen's Conflict - Maraulang, Maraulang (State Islamic Institute of Palopo, 2025)
This study aims to provide a comprehensive overview of the historical context and evolution of Yemen's conflict, identifying and analyzing key themes and contributing factors and highlighting gaps in current research to suggest areas for future study. The methodology involved a meticulous and systematic literature selection process, prioritizing peer-reviewed journal articles, academic books, and reports from reputable organizations, focusing on historical and contemporary analyses. The data was gathered from various academic and reputable databases, including JSTOR, Google Scholar, PubMed, and Web of Science, and analyzed using thematic and content analysis. The results indicate that Yemen's conflict is driven by a complex interplay of political instability, economic hardship, social and cultural dimensions, and foreign intervention. Key findings highlight the chronic political fragmentation, economic dependency on oil revenues, significant social factors such as tribal affiliations and sectarian divides, and the complicating role of external influences. The study identifies gaps in research, particularly the need for in-depth studies on the humanitarian impact, local peacebuilding efforts, and long-term environmental impacts. Addressing these gaps will provide a more holistic understanding of Yemen's conflict and inform effective policy responses.